Environmental controls of lucerne (Medicago sativa L.) growth across a climatic and edaphic gradient - Druille, Magdalena (2017)
Fil: Druille, Magdalena. Universidad de Buenos Aires. Facultad de Agronomía. Departamento de Producción Animal. Buenos Aires, Argentina.